Number and size of suspended particulate matter (SPM) from a mining trial at the Belgian (GSR) contract area in the Clarion Clipperton Zone during the MANGAN 2021 (IP21) expedition - Iason-Zois Gazis; Benjamin Gillard; Laurenz Thomsen; Karl Heger; Jochen Mohrmann; Matthias Haeckel; Jens Greinert (PANGAEA, 2025)
Number (# L-1) and size (μm) of suspended particulate matter (SPM) obtained with the PartiCam system at < 1 m above the seafloor and 180 m from the collector impact site in the Belgian (GSR) contract area in the Clarion Clipperton Zone (CCZ) during the MANGAN 2021 (IP21) expedition. The data format is also compatible with the Digital Earth Viewer (https://digitalearthviewer-glodap.geomar.de/).